O coordenador pedagógico e o seu papel na formação continuada em serviço do professor de educação infantil (creche) - Zumpano, Viviani Aparecida Amabile (2010)
The objective of this research was to investigate the role of educational coordinators in the on-the-job continued education of child education teachers that work in daycare centers. The research focused on two participants, who work as educational coordinators in two daycare centers belonging to the private indirectly-accredited network, both connected to the Municipality of São Paulo. As instrument for data collection, we made use of two semistructured interviews. The referential adopted was the psychogenetical theory of Henri Wallon, and also the contribution of the studies conducted by Placco, Imbernòn, Tardif and Canário in the area of teacher training. Data attained by means of testimonials from participants were made explicit in units of meaning and later turned into three themes. Interpretation of the data attained showed that the participating educational coordinators considered their role as key, articulating and integrating in the on-the-job continued education of the teachers they followed. They perceive themselves as a model of conduct and action for teachers and that the educational coordinator is an educator in the process of being an educator, that is, they are in constant professional constitution. Some of the elements related to the role of the educational coordinator raised by participants were: close monitoring, paying close attention, observing teachers as individuals and their work, perceiving their educational needs; making teachers aware of their educational role in the child learning process; working with the self-esteem and the autonomy of educators; encouraging teachers in the process of reflecting over their practice; articulating the interpersonal relations; providing the theoretical instruments to educators and verifying how they appropriate the theory and apply it in practice; encouraging teachers to be subjects of their educational process; working professionalism. The key challenges showed by participants were: having daycare educators perceive themselves as teachers; enabling teachers to put into practice the contents they acquired in their education; encouraging them to go beyond an existing welfare-oriented vision in the work of daycare teachers; making teachers aware of their role without making use of authority or imposition; dealing with the routine and the unexpected that occurs on the day-to-day of daycare centers and managing the feeling of solidarity that permeates their work as educational coordinators. The coordinating participants also brought some personal educational needs: seeking education in the area of linguistics to improve the quality of communication with parents, teachers and other professionals who work in daycare centers; seeking specific education for educational coordinators directed to reflection in order to better direct teachers reflexive process, as well as developing the skills to solve conflicts that emerge on the day-to-day of daycare centers and enhance their technical skills. Participants answers indicate that they feel responsible and committed to the education of the educators they monitor, trying to solve the challenges that come up in this process and seeking for new alternative actions that may affect educators, verifying how these professionals get hold of their on-the-job continued education